Jio Telecom: Navigating the Dynamic Landscape of Indian Telecommunications - M. Valliammal, S. K. Manivannan, (European Economic Letters (EEL), 2024)
This research explores Reliance Jio Infocomm Ltd's transformative journey in India's telecommunications sector. As the leading 4G network provider, Jio, a subsidiary of Reliance Industries, rapidly gained popularity since its 2016 launch. Operating a national LTE network with plans for 5G and 6G, Jio boasts a customer base exceeding 426.2 million, ranking as the third-largest global telecommunication operator. The study employs a literature review to identify Jio's growth trends and strategies, drawing insights from diverse sources. It provides a backdrop of India's telecom sector, emphasizing Jio's disruptive marketing strategy, target audience, and digital presence. As the sector anticipates 500 million new internet users, the research positions Jio as a masterclass in market disruption and growth.